Pre-Service Bahasa Teachers’ Readiness for the Integration of Bengkulu Ethnopedagogy in the Merdeka Curriculum to Reinvigorate Local Wisdom in Modern Education - Friantary, Heny; Manjato, Ajat; Saputra, Ade Bayu; Saputra, Hendro Ade (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study critically analyzes the readiness of pre-service teachers to integrate Bengkulu ethnopedagogy into modern classroom settings. Using a mixed-methods approach, data were collected from 150 pre-service teachers at several universities in Bengkulu through a readiness scale survey and semi-structured interviews. This study employs a mixed-methods approach by collecting data from 150 pre-service teachers in Bengkulu through readiness scale surveys and semi-structured interviews, which were subsequently analyzed using descriptive-ANOVA anlysis and thematic analysis. The findings reveal a significant gap: while pre-service teachers possess high affective readiness (valuing local culture), their pedagogical readiness specifically in transforming indigenous knowledge into structured lesson plans remains moderate to low. Key barriers identified include the lack of standardized ethnopedagogical teaching materials and a perceived tension between traditional values and global 21st-century skill requirements. This research suggests that teacher education programs must move beyond theoretical appreciation and provide practical frameworks for